Penerapan Konsep Sustainable pada Bangunan Cohousing untuk Masyarakat Milenial - Hendriwati, Felisitas Sekar; Mudra, I Ketut; Wirawibawa, Ida Bagus Gde (Jurnal Arsitektur Universitas Udayana, 2022)
Cohousing is a type of collaborative housing that support the resident to actively participate in design and environment management theirself. Along with the decrease of land and the high price of land in Jakarta, then cohousing could be the answer of the land crisis needs and residence for milenial with more affordable prices. The method used is research development and design method. One of the purpose is to build sustainbale lifestyle or support the enviromentally friendly itself. The lifestyle of cohousing's resident would be different compared to resident in another residence because cohousing's resident could have sosialist lifestyle, environmentally friendly and more efficient. Another advantage in cohousing is the resident could freely fulfill their residence needs. Sustainable system in cohousing can be taken from several aspects such as environment, resident itself, resources, financial, and community.